MYC promotes group 3 medulloblastoma cell proliferation and alleviates ROS-induced cell death by upregulating transketolase - Shizun Wang; Dan Zhang; Chunlong Wang; Yuqin Liu (Acta Neuropathologica Communications, 2025)
Abstract Medulloblastoma is a common embryonic malignant tumor in children. Patients with Group 3 medulloblastoma exhibit the poorest prognosis among all subgroups, and approximately 20% of these patients carry an amplification of MYC. Metabolic reprogramming, a hallmark of cancer, includes the pentose phosphate pathway (PPP) as a branch of glucose metabolism, providing cells with ribose-5-phosphate (R5P) and nicotinamide adenine dinucleotide phosphate (NADPH). The role of PPP in medulloblastoma remains unclear. In this study, we utilized transcriptomic data to identify that high expression of transketolase (TKT) correlates with worse overall survival (OS) in Group 3 patients. We found that TKT promotes proliferation of Group 3 medulloblastoma cell line cells both in vitro and in vivo. Additionally, TKT enhances R5P synthesis, increasing the proportion of S-phase cells and promoting proliferation. TKT also facilitates NADPH synthesis, which reduces intracellular reactive oxygen species (ROS) levels, inhibits ROS-induced cell death, and strengthens cellular resistance to ROS-induced injury. Subsequently, we demonstrated that inhibition of MYC leads to decreased TKT protein levels, and MYC promotes cell proliferation and suppresses cell death via TKT. Chromatin immunoprecipitation-quantitative real-time polymerase chain reaction (ChIP-qPCR) confirmed that employing the antibody targeting MYC enables the immunoprecipitation of DNA localized to the promoter region of TKT. Using luciferase assay and western blot, we verified that MYC and specificity protein 1 (SP1) co-regulate the transcription of TKT and consequently elevates TKT protein levels. Collectively, our study reports that MYC facilitates the proliferation of Group 3 medulloblastoma cells and mitigates ROS-induced damage through TKT, suggesting TKT as a potential therapeutic target for MYC-driven Group 3 medulloblastoma.